Avaliação da qualidade do azeite durante o processo de fritura - Carapinha, P. (2013)
Olive oil is the main lipid source in the Mediterranean diet. Due to its richness in monounsaturated fatty acids and in natural antioxidants, the olive oil is highly resistant to oxidation and, therefore, it is an excellent oil to be used in deep frying processes. The aim of the present study was to investigate the quality evolution of two commercial olive oils (extra virgin olive oil and olive oil) during heating at 180ºC (±2ºC) along 63 h, and frying processes of pre-fried frozen French fries in a domestic frying pan. Viscosity, acidity, peroxide index, p-anisidine index, UV absorbance values (232 and 270 nm), polar compounds and fatty acid composition were determined in the different olive oil samples Along heating and frying cycles, an increase of the physico-chemical parameters, as a consequence of several factors, namely high temperature and the presence of oxygen that contribute for lipid oxidation. However, in frying experiments lower increase in physico-chemical parameters were observed as a consequence of a temperature decrease in frying medium when the frozen food was immerged